Desulfonation low-viscosity high-shear strong-inhibition water-based drilling fluid

By developing desulfonated low viscosity, high cutting strength inhibiting water-based drilling fluid, using specific combinations of cutters, inhibitors and lubricants, the problem of insufficient rheology and inhibition in high-temperature water-sensitive formations is solved. , achieving stable well wall, environmental protection and efficient drilling.

CN119391390AActive Publication Date: 2025-02-07XINJIANG BEIKEN ENERGY ENG +1

Patent Information

Application Number
CN202510000160.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-02-07
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

The existing water-based drilling fluid lacks rheology, inhibition and temperature resistance in high-temperature and water-sensitive formations, resulting in instability of the well wall and environmental protection problems.

Method used

Develop a desulfonated low viscosity high cutting strength inhibiting water-based drilling fluid, by using a mixture of keratinous gum, de-adjustment and vealan gum as a cutting agent, polyethyleneimine graft copolymer and hexanediamine The mixture acts as an inhibitor, and the mixture of polyethylene glycol borate, fatty alcohol polyoxyethylene ether and nanosilicon nitride serves as lubricant, combined with barite to achieve the desired density.

Benefits of technology

The rheological characteristics of low viscosity and high shearing under high temperature conditions are achieved, which significantly inhibits the expansion and dispersion of formation water-sensitive minerals, maintains the stability of the well wall, improves drilling efficiency, and has good environmental protection and biodegradation performance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a desulfonation low-viscosity high-shear strong-inhibition water-based drilling fluid, and belongs to the technical field of oil field chemistry of oil and gas drilling engineering. The de-sulfonation low-viscosity high-shear strong-inhibition water-based drilling fluid is prepared from the following raw materials in parts by mass: 100 parts of water, 0.5 to 1.0 part of a pH regulator, 1 to 3 parts of a lubricant, 0.5 to 0.7 part of a shear strength improving agent, 2 to 4 parts of a filtrate reducer, 2 to 4 parts of an inhibitor, 5 to 15 parts of an auxiliary inhibitor, 1 to 3 parts of a dispersing agent and barite, the barite is not limited in parts, and the barite is added until the required density is reached. The desulfonation low-viscosity high-shear strong-inhibition water-based drilling fluid can effectively inhibit expansion and dispersion of formation water-sensitive minerals in a high-temperature water-sensitive formation environment, maintain the stability of a well wall, guarantee the cleanness of a well hole and improve the drilling efficiency, is environment-friendly and biodegradable, and meets green, safe and efficient drilling requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oilfield chemistry for oil and gas drilling engineering, and in particular to a desulfonated low-viscosity high-shear strength inhibited water-based drilling fluid. Background Art

[0002] Drilling fluid plays a vital role in the drilling process of resources such as oil and natural gas. Its main functions include carrying cuttings, cooling and lubricating the drill bit, maintaining wellbore stability, and balancing formation pressure. With the advancement of drilling technology, the complexity of the drilling environment, and the stringent environmental protection requirements, the performance requirements for drilling fluids are also increasing. Especially for long horizontal well construction operations in high-temperature and water-sensitive formations, although conventional water-based drilling fluids have certain environmental advantages, their rheology, inhibition and temperature resistance are still insufficient.

[0003] As we all know, the plastic viscosity and dynamic shear force of drilling fluid are important indicators for evaluating its rheological properties. Low plastic viscosity helps reduce circulation pressure loss, reduce pumping energy consumption, and improve drilling efficiency. Drilling fluid with high dynamic shear can maintain a high suspension capacity under low-speed conditions, which helps to reduce the settling speed of cuttings and ensure that the cuttings are effectively carried to the ground. Especially for long horizontal well drilling operations, achieving low plastic viscosity and high dynamic shear rheological properties of drilling fluid is the key.

[0004] For water-sensitive formations, the inhibition of drilling fluid is crucial, which is related to the expansion and dispersion of water-sensitive minerals (such as shale, mudstone, etc.) in the formation. Insufficient inhibition will cause the formation rock to absorb water, expand and disintegrate, causing wellbore instability and affecting the smooth progress of drilling operations. Therefore, the development of drilling fluid with strong inhibition is of great significance to ensure wellbore stability and improve drilling safety and efficiency.

[0005] At the same time, high temperature conditions pose a major challenge to the above rheological and inhibitory properties of drilling fluids. Although the traditional sulfonation modification method can significantly improve the temperature resistance of drilling fluid materials, the introduced sulfonic acid groups make the polymer materials difficult to degrade, making it difficult to handle waste and drill cuttings in the later stage. Even if they are handled, sulfur-containing byproducts will be produced, which is not conducive to ecological environmental protection.

[0006] Based on this, a desulfonated, low-viscosity, high-shear-strength inhibited water-based drilling fluid was developed, which can not only solve environmental problems, but also meet the performance requirements of drilling fluids for shale water-sensitive formations and long horizontal wells, thereby improving drilling efficiency and safety. It is of great significance to achieve green, safe and efficient drilling. Summary of the invention

[0007] In view of this, the purpose of the present invention is to provide a desulfonated low-viscosity high-shear strength inhibited water-based drilling fluid. The drilling fluid provided by the present invention can effectively inhibit the expansion and dispersion of water-sensitive minerals in the formation in a high-temperature water-sensitive formation environment, maintain the stability of the well wall, ensure the cleanliness of the wellbore, improve the drilling efficiency, and is environmentally friendly and biodegradable, meeting the requirements of green, safe and efficient drilling.

[0008] In order to achieve the above object, the present invention provides the following technical solutions: A desulfonated low-viscosity high-shear strength inhibiting water-based drilling fluid, wherein the raw materials include, by weight: 100 parts of water, 0.5-1.0 parts of a pH adjuster, 0.5-0.7 parts of a shear enhancer, 2-4 parts of a fluid loss reducer, 2-4 parts of an inhibitor, 5-15 parts of an auxiliary inhibitor, 1-3 parts of a dispersant, 1-3 parts of a lubricant, and barite; the barite is not limited in number and is added until the required density is reached; The cutting agent is a mixture of 20 to 30 parts of sclerotium gum, 20 to 30 parts of diutan gum and 40 to 60 parts of welan gum.

[0009] In the present invention, the density of the desulfonated low-viscosity high-shear strength inhibiting water-based drilling fluid is 1.1-1.7 g / cm 3 .

[0010] The present invention discloses the following technical effects: The desulfonated low-viscosity and high-shear-inhibiting water-based drilling fluid provided by the present invention can achieve the rheological properties of low viscosity and high shear under the action of the shear-enhancing agent, that is, it has significant shear-thinning behavior, maintains good fluidity and cuttings transport performance during normal drilling, and has the ability to suspend cuttings during the stop cycle period, avoiding the sedimentation of cuttings and causing drilling blockage. The desulfonated low-viscosity and high-shear-inhibiting water-based drilling fluid provided by the present invention also has excellent inhibition performance, and mainly achieves clay hydration inhibition through the following aspects: First, the inhibitor polyamine functional group characteristics are utilized to effectively adsorb on the surface of clay particles to form a protective layer, preventing water molecules from entering the clay layer, and further compressing the diffuse double layer under the action of cationic ammonium, thereby inhibiting clay hydration; second, a large number of cations provided by the auxiliary inhibitor are combined to strengthen the electrostatic interaction, and the mosaic effect of potassium ions is utilized to play an auxiliary inhibition effect; third, the adsorption and film-forming characteristics of the dispersant can synergistically enhance the inhibition of clay hydration. The desulfonated low-viscosity and high-shear strength inhibiting water-based drilling fluid provided by the present invention adopts a desulfonation design, which avoids the problem that traditional sulfonated polymers are difficult to degrade, makes the drilling fluid more environmentally friendly, reduces the negative impact on the ecological environment, and meets the requirements of green drilling.

[0011] The desulfonated low-viscosity and high-shear-strength inhibiting water-based drilling fluid of the present invention has a dynamic-plastic ratio of more than 1.0, an API filtration loss of less than 3.5 mL, an extreme pressure friction coefficient of ≤0.08, an apparent viscosity increase rate after 20% sodium-based bentonite contamination of less than 11%, a shale rolling recovery rate of more than 95%, a biodegradation index of more than 25%, and an unweighted dry basis sulfur content of 0. While meeting the safety operation requirements for long horizontal wells in high-temperature and water-sensitive formations, it also has significant environmental protection and biodegradability. DETAILED DESCRIPTION

[0012] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0013] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0014] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0015] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0016] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0017] The invention provides a desulfonated low-viscosity high-shear strength inhibiting water-based drilling fluid. The raw materials include, by weight, 100 parts of water, 0.5-1.0 parts of a pH regulator, 0.5-0.7 parts of a shearing agent, 2-4 parts of a fluid loss reducer, 2-4 parts of an inhibitor, 5-15 parts of an auxiliary inhibitor, 1-3 parts of a dispersant, 1-3 parts of a lubricant and barite; the barite is not limited in number and is added to a desired density.

[0018] In the present invention, the water is fresh water or sea water.

[0019] In some embodiments of the present invention, the pH adjuster is a mixture of 40 to 60 parts of sodium hydroxide and 40 to 60 parts of sodium carbonate, by mass.

[0020] Sodium hydroxide can provide a strong alkaline environment for the system. On the one hand, it can prevent acidic substances from corroding the drill tools. On the other hand, each component material can play its best role in an alkaline environment. Sodium carbonate can react with high-valent mineral ions to form water-insoluble precipitates, preventing these ions from affecting the performance of other additive materials.

[0021] In some embodiments of the present invention, the cutting agent is a mixture of 20-30 parts of sclerotium gum, 20-30 parts of diutan gum and 40-60 parts of welan gum, calculated by weight.

[0022] Sclerotium gum, diutan gum and welan gum are all microbial polysaccharide polymers. When used in combination, they can significantly increase the dynamic shear force of drilling fluid while controlling the viscosity at a low level, which is beneficial for suspending cuttings, improving the wellbore cleaning effect, and improving drilling efficiency. These polysaccharide polymers are all prepared by microbial fermentation, are non-toxic, biodegradable, and are beneficial for protecting the ecological environment.

[0023] In some embodiments of the present invention, the raw materials of the fluid loss reducer include, by weight: 15-25 parts of fulvic acid, 100 parts of water, 1-3 parts of chitosan, 1-3 parts of γ-methacryloxypropyltrimethoxysilane, 100 parts of ethanol aqueous solution containing acetic acid, 5-10 parts of acrylic acid, 10-20 parts of N-vinyl pyrrolidone, 5-12 parts of dimethyldiallylammonium chloride and 0.1-0.3 parts of ammonium persulfate; The preparation method of the fluid loss reducer comprises the following steps: dissolving chitosan in a fulvic acid aqueous solution to obtain a fulvic acid-chitosan mixed solution; Dissolving γ-methacryloxypropyltrimethoxysilane in an ethanol aqueous solution containing acetic acid, and then performing a hydrolysis reaction to obtain a pre-hydrolyzed silane coupling agent; Adding the pre-hydrolyzed silane coupling agent to the fulvic acid-chitosan mixed solution to react and obtain an intermediate product; Acrylic acid, N-vinyl pyrrolidone and dimethyl diallyl ammonium chloride are dissolved in water, and the pH value is adjusted to alkaline, and then the intermediate product is added under stirring conditions. Under the protection of an inert atmosphere, ammonium persulfate is added to the reaction system to carry out a polymerization reaction 1 to obtain the fluid loss reducer.

[0024] The present invention does not specifically limit the preparation method of the fulvic acid aqueous solution, and the technical means well known to those skilled in the art can be used, for example, adding fulvic acid to water and stirring to dissolve. The present invention does not specifically limit the manner in which chitosan is dissolved in the fulvic acid aqueous solution, and the technical means well known to those skilled in the art can be used, for example, stirring to dissolve.

[0025] In some embodiments of the present invention, in the ethanol aqueous solution containing acetic acid, the content of acetic acid is 1% v / v, and the content of ethanol is 85% v / v.

[0026] In some embodiments of the present invention, the hydrolysis reaction is carried out at a temperature of 40-50° C. and for a time of 3-5 h.

[0027] In some embodiments of the present invention, when the pre-hydrolyzed silane coupling agent is added to the fulvic acid-chitosan mixture for reaction, the reaction temperature is 60-70°C and the reaction time is 10-20 hours. After the reaction is completed, the steps of cooling to room temperature, removing the solvent by centrifugation, washing with anhydrous ethanol, and vacuum drying are also included.

[0028] In some embodiments of the present invention, adjusting the pH value to alkaline is adjusting the pH to 7-8. The present invention does not specifically limit the alkali solution used to adjust the pH to alkaline, and any alkali solution well known to those skilled in the art can be selected, for example: 0.1 mol / L sodium hydroxide aqueous solution.

[0029] In some embodiments of the present invention, the reaction temperature of the polymerization reaction 1 is 65-75°C and the time is 3-5h; after the polymerization reaction 1 is completed, it also includes the steps of cooling to room temperature, washing with deionized water, vacuum filtration, and vacuum drying.

[0030] The fluid loss reducer provided by the present invention is a composite modified product of natural polymer humic acid and chitosan. The abundant carboxyl groups and phenolic hydroxyl groups in humic acid can form a strong adsorption effect with the minerals or drill cuttings particles on the well wall, which helps to form a dense protective film on the well wall surface and reduce the penetration of drilling fluid; and the addition of chitosan is conducive to enriching the network structure and increasing the viscosity of the filtrate, thereby further reducing the filtrate penetration rate. Through the cross-linking effect of the silane coupling agent, on the one hand, the two natural polymers can be connected and enhanced into a network structure coverage, and on the other hand, functional groups can be introduced through graft copolymerization to improve water-soluble dispersion and temperature and salt resistance. For example, the introduction of acrylic acid is conducive to improving the distribution of carboxyl groups, thereby improving water-soluble dispersibility; and the introduction of N-vinyl pyrrolidone utilizes the rigid structure of its five-membered ring to maintain the stability of the polymer structure at high temperatures; in addition, dimethyldiallylammonium chloride provides cations, which helps to improve salt resistance and stability.

[0031] In some embodiments of the present invention, the inhibitor is a mixture of 70-80 parts of polyethyleneimine graft copolymer and 20-30 parts of hexamethylenediamine, by weight.

[0032] The inhibitor provided by the present invention is a composite product of a macromolecular polyethyleneimine graft copolymer and a small molecule hexamethylenediamine. The polyethyleneimine graft copolymer contains ether bonds, amide groups, carboxyl groups and cationic ammonium, etc., and exhibits extremely strong hydrophilicity and adsorption, and can be adsorbed on the surface of clay particles to inhibit the hydration and dispersion of clay; the cationic ammonium therein can neutralize the negative charge on the surface of the clay, compress the diffusion double electric layer, and thus inhibit the hydration and expansion of the clay. In addition, due to its small molecular weight, hexamethylenediamine can be uniformly adsorbed on the surface of clay particles. On the one hand, it utilizes the positively charged characteristic of the terminal amino functional group after protonation in the solution, and enters the clay layer under the drive of the chemical potential difference, and prevents the separation of the clay layer under the electrostatic interaction, thereby playing a strengthening inhibitory effect.

[0033] In some embodiments of the present invention, the raw materials of the polyethyleneimine graft copolymer include, by weight: 100 parts of water, 40-60 parts of polyethyleneimine, 10-20 parts of maleic anhydride, 15-25 parts of dimethyldiallylammonium chloride and 0.6-0.8 parts of potassium persulfate.

[0034] In some embodiments of the present invention, the method for preparing the polyethyleneimine graft copolymer comprises the following steps: Conducting amidation reaction between polyethyleneimine and maleic anhydride; After the amidation reaction is completed, water and dimethyldiallylammonium chloride are added to the reaction system, and potassium persulfate is added under an inert atmosphere to carry out polymerization reaction 2 to obtain the polyethyleneimine graft copolymer.

[0035] In some embodiments of the present invention, polyethyleneimine and maleic anhydride are subjected to an amidation reaction, specifically: polyethyleneimine is heated to 65-75° C. in a water bath under stirring conditions, nitrogen is passed to deoxygenate, and then maleic anhydride is slowly added to carry out an amidation reaction; the temperature of the amidation reaction is 70-80° C., and the time is 3-5 hours.

[0036] In some embodiments of the present invention, the polymerization reaction 2 is carried out at a temperature of 60-70° C. and for a time of 2-4 hours.

[0037] In some embodiments of the present invention, the auxiliary inhibitor is a mixture of 10-20 parts of sodium chloride, 20-30 parts of potassium chloride, 30-40 parts of sodium formate and 20-30 parts of potassium formate, calculated by weight.

[0038] Sodium chloride and potassium chloride provide sodium and potassium cations, respectively, which can help improve the inhibition of drilling fluids, especially potassium ions, because they can be embedded in clay layers, thus effectively inhibiting clay expansion. In addition to providing sodium and potassium cations, sodium formate and potassium formate can also provide formate anions, which have the function of scavenging free radicals and can effectively improve the resistance of the cutting agent to oxidative degradation, thereby improving the temperature stability.

[0039] In some embodiments of the present invention, the raw materials of the dispersant include, by weight: 100 parts of water, 20 to 30 parts of ethanolamine, 20 to 30 parts of itaconic anhydride, 3 to 5 parts of vinylphosphonic acid, 3 to 5 parts of N-vinyl pyrrolidone and 0.5 to 1.0 parts of ammonium persulfate; The preparation method of the dispersant comprises the following steps: Conducting an amidation reaction between ethanolamine and itaconic anhydride; After the amidation reaction is completed, water, vinylphosphonic acid and N-vinyl pyrrolidone are added to the reaction system, and potassium persulfate is added under an inert atmosphere to carry out polymerization reaction 3 to obtain the dispersant.

[0040] In some embodiments of the present invention, the amidation reaction of ethanolamine and itaconic anhydride is specifically as follows: ethanolamine is heated to 70-75°C in a water bath under stirring conditions, nitrogen is passed to deoxygenate, and then itaconic anhydride is slowly added to carry out the amidation reaction; the temperature of the amidation reaction is 80-90°C, and the time is 2-4 hours.

[0041] In some embodiments of the present invention, the polymerization reaction 3 is carried out at a temperature of 70-80° C. and for a time of 2-3 h.

[0042] The dispersant provided by the present invention contains a large number of functional groups such as carboxyl, hydroxyl, phosphonic acid, amide and pyrrolidone ring. On the one hand, through the strong hydrophilicity and adsorption of polar groups such as hydroxyl, amide and pyrrolidone ring and the electrostatic repulsion of carboxyl and phosphonic acid, the aggregation of solid phase particles such as drill cuttings and barite in the drilling fluid can be effectively prevented, and the particles can be uniformly dispersed through the steric hindrance effect, thereby reducing the sedimentation risk of solid phase particles, which is beneficial to wellbore cleaning; on the other hand, the phosphonic acid, carboxyl and amide groups in the dispersant form a stable protective layer through complexation with cations in clay minerals, surface adsorption and hydrogen bonding, etc., to prevent water molecules from entering the clay interlayer, thereby inhibiting the water absorption and expansion and dispersion of clay, and assisting in improving the inhibition of drilling fluid, avoiding the occurrence of problems such as drilling fluid thickening or well wall instability caused by hydration of high-clay drill cuttings or well wall rocks. In addition, the introduction of phosphonic acid groups also gives the dispersant the effect of chelating high-valent cations such as calcium and magnesium, which can effectively enhance the anti-calcium and magnesium ion pollution performance of drilling fluid.

[0043] In some embodiments of the present invention, the lubricant is a mixture of 40-45 parts of polyethylene glycol borate, 45-50 parts of fatty alcohol polyoxyethylene ether and 5-15 parts of nano silicon nitride, calculated by weight.

[0044] Polyethylene glycol borate forms a stable lubricating film between the drill bit and the well wall, reducing metal contact and friction coefficient; fatty alcohol polyoxyethylene ether acts as a surfactant to reduce surface tension, enhance the uniformity and stability of the lubricating film, etc.; nano silicon nitride acts as a solid lubricant to fill tiny bumps, reduce friction, and improve the wear resistance of the lubricating film. The synergistic effect of each component further improves the comprehensive performance of the lubricant, showing excellent lubrication effect under complex drilling conditions.

[0045] The desulfonated low-viscosity high-shear strength inhibited water-based drilling fluid provided by the present invention can be prepared by a conventional preparation method.

[0046] The technical solutions described in the present invention, unless otherwise specified, are all conventional solutions in the art, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.

[0047] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments. Example 1

[0048] A desulfonated low-viscosity high-shear strength inhibited water-based drilling fluid, the raw materials of which are as follows, calculated by weight: Fresh water: 100 parts pH adjuster: 0.5 parts Cutting agent: 0.5 parts Fluid loss reducer: 2 parts Inhibitor: 2 parts Auxiliary inhibitor: 5 parts Dispersant: 1 part Lubricant: 1 part Barite: Add weight to the drilling fluid density of 1.1g / cm 3 The pH adjuster is a mixture of 40 parts by mass of sodium hydroxide and 60 parts by mass of sodium carbonate.

[0049] The cutting agent is a mixture of 20 parts of sclerotium gum, 20 parts of diutan gum and 60 parts of welan gum by weight.

[0050] The raw materials of the fluid loss reducer are as follows: 15 parts of fulvic acid, 100 parts of deionized water, 1 part of chitosan, 1 part of γ-methacryloxypropyltrimethoxysilane, 100 parts of 85% ethanol aqueous solution (1% acetic acid), 5 parts of acrylic acid, 10 parts of N-vinyl pyrrolidone, 5 parts of dimethyldiallylammonium chloride and 0.1 parts of ammonium persulfate by mass. The preparation method of the above-mentioned fluid loss reducing agent is: First, dissolve fulvic acid in deionized water, stir for 30 minutes, then add chitosan, continue stirring for 1 hour, and transfer the fulvic acid-chitosan mixture to a four-necked round-bottom flask. Then dissolve γ-methacryloxypropyltrimethoxysilane in an 85% ethanol aqueous solution containing 1% acetic acid, then slowly heat to 40°C under stirring conditions, and hydrolyze for 3 hours; then slowly add the pre-hydrolyzed silane coupling agent to the fulvic acid-chitosan mixture, continue stirring and heat to 60°C, stop heating after 10 hours of reaction, and cool to room temperature; remove the solvent by centrifugation, wash with anhydrous ethanol several times, and then vacuum dry to obtain the intermediate product; Secondly, acrylic acid, N-vinyl pyrrolidone and dimethyldiallylammonium chloride were dissolved in deionized water in advance, and the pH value was adjusted to 7 with 0.1 mol / L sodium hydroxide aqueous solution. After stirring for 10 minutes, the mixed solution was transferred to a four-necked round-bottom flask; then, the intermediate product obtained in the above step was added thereto under stirring, nitrogen was passed to deoxygenate, the temperature was raised to 65° C., and ammonium persulfate was dissolved in deionized water and then added dropwise thereto to initiate a polymerization reaction for 1, which lasted for 3 hours, then the reaction was stopped and cooled to room temperature; finally, the mixture was washed with deionized water for multiple times, vacuum filtered, vacuum dried and crushed, and the obtained product was a filtrate reducer.

[0051] The inhibitor is a mixture of 70 parts of polyethyleneimine graft copolymer and 30 parts of hexamethylenediamine by mass; The raw materials of polyethyleneimine graft copolymer are: 100 parts of deionized water, 40 parts of polyethyleneimine, 10 parts of maleic anhydride, 15 parts of dimethyldiallylammonium chloride, and 0.6 parts of potassium persulfate; The preparation method of the above-mentioned polyethyleneimine graft copolymer is: First, polyethyleneimine was added to a four-necked flask, and the temperature was raised to 65°C in a water bath under stirring conditions, and nitrogen was passed to deoxygenate, and then maleic anhydride was slowly added to carry out an amidation reaction, and the reaction temperature was controlled at 70°C and the reaction time was 3 hours to obtain an intermediate product; Secondly, the flask containing the intermediate product was cooled to room temperature, and deionized water and dimethyldiallyl ammonium chloride were slowly added thereto, stirred for 30 minutes, nitrogen was passed to deoxygenate, and potassium persulfate was then added to initiate the polymerization reaction 2. The reaction temperature was controlled at 60°C and the reaction time was 2 hours. The final product was a polyethyleneimine graft copolymer.

[0052] The auxiliary inhibitor is a mixture of 10 parts of sodium chloride, 20 parts of potassium chloride, 40 parts of sodium formate and 30 parts of potassium formate, by mass.

[0053] The raw materials of the dispersant are as follows, by weight: 100 parts of deionized water, 20 parts of ethanolamine, 20 parts of itaconic anhydride, 3 parts of vinylphosphonic acid, 3 parts of N-vinylpyrrolidone, and 0.5 parts of ammonium persulfate; The above dispersant preparation method is: First, ethanolamine was added to a four-necked flask, and the temperature was raised to 70°C in a water bath under stirring conditions, and nitrogen was passed to deoxygenate, and then itaconic anhydride was slowly added to carry out an amidation reaction, and the reaction temperature was controlled at 80°C and the reaction time was 2h to obtain an intermediate product; Secondly, the flask containing the intermediate product was cooled to room temperature, and deionized water, vinylphosphonic acid and N-vinylpyrrolidone were slowly added thereto, stirred for 20 minutes, and nitrogen was passed to deoxygenate. Subsequently, ammonium persulfate was added to initiate the polymerization reaction 3, and the reaction temperature was controlled at 70°C and the reaction time was 2 hours. Finally, the product obtained was the dispersant.

[0054] The lubricant is a mixture of 40 parts of polyethylene glycol borate, 45 parts of fatty alcohol polyoxyethylene ether and 15 parts of nano silicon nitride by weight.

[0055] The drilling fluid density provided in this embodiment is 1.1 g / cm 3 , the hot rolling temperature of the drilling fluid is 30℃. Example 2

[0056] A desulfonated low-viscosity high-shear strength inhibited water-based drilling fluid, the raw materials of which are as follows by weight: Seawater: 100 parts pH adjuster: 1.0 part Cutting agent: 0.7 parts Fluid loss reducer: 4 parts Inhibitor: 4 parts Auxiliary inhibitor: 15 parts Dispersant: 3 parts Lubricant: 3 parts Barite: Add weight to the drilling fluid density of 1.3g / cm 3 The pH adjuster is a mixture of 60 parts by mass of sodium hydroxide and 40 parts by mass of sodium carbonate.

[0057] The cutting agent is a mixture of 30 parts of sclerotium gum, 30 parts of diutan gum and 40 parts of welan gum by weight.

[0058] The raw materials of the fluid loss reducer are, by mass, 25 parts of fulvic acid, 100 parts of deionized water, 3 parts of chitosan, 3 parts of γ-methacryloxypropyltrimethoxysilane, 100 parts of 85% ethanol aqueous solution (1% acetic acid), 10 parts of acrylic acid, 20 parts of N-vinyl pyrrolidone, 12 parts of dimethyldiallylammonium chloride and 0.3 parts of ammonium persulfate.

[0059] The preparation method of the above-mentioned fluid loss reducing agent is: First, dissolve fulvic acid in deionized water, stir for 60 minutes, then add chitosan, continue stirring for 2 hours, and transfer the fulvic acid-chitosan mixture to a four-necked round-bottom flask. Then dissolve γ-methacryloxypropyltrimethoxysilane in an 85% ethanol aqueous solution containing 1% acetic acid, then slowly heat to 50°C under stirring conditions, and hydrolyze for 5 hours; then slowly add the pre-hydrolyzed silane coupling agent to the fulvic acid-chitosan mixture, continue stirring and heat to 70°C, stop heating after 20 hours of reaction, and cool to room temperature; remove the solvent by centrifugation, wash with anhydrous ethanol several times, and then vacuum dry to obtain the intermediate product; Secondly, acrylic acid, N-vinyl pyrrolidone and dimethyldiallylammonium chloride were dissolved in deionized water in advance, and the pH value was adjusted to 8 with 0.1 mol / L sodium hydroxide aqueous solution. After stirring for 30 minutes, the mixed solution was transferred to a four-necked round-bottom flask; then, the intermediate product obtained in the above step was added thereto under stirring, nitrogen was passed to deoxygenate, the temperature was raised to 75°C, and ammonium persulfate was dissolved in deionized water and then added dropwise thereto to initiate a polymerization reaction for 1, which lasted for 5 hours, then the reaction was stopped and cooled to room temperature; finally, the mixture was washed with deionized water for multiple times, vacuum filtered, vacuum dried and crushed, and the obtained product was a filtrate reducer.

[0060] The inhibitor is a mixture of 80 parts of polyethyleneimine graft copolymer and 20 parts of hexamethylenediamine by weight; The raw materials of polyethyleneimine graft copolymer are: 100 parts of deionized water, 60 parts of polyethyleneimine, 20 parts of maleic anhydride, 25 parts of dimethyldiallylammonium chloride and 0.8 parts of potassium persulfate; The preparation method of the above-mentioned polyethyleneimine graft copolymer is: First, polyethyleneimine was added to a four-necked flask, and the temperature was raised to 75°C in a water bath under stirring conditions, and nitrogen was passed to deoxygenate, and then maleic anhydride was slowly added to carry out an amidation reaction, and the reaction temperature was controlled at 80°C and the reaction time was 5 hours to obtain an intermediate product; Secondly, the flask containing the intermediate product was cooled to room temperature, and deionized water and dimethyldiallyl ammonium chloride were slowly added thereto, stirred for 60 minutes, nitrogen was passed to deoxygenate, and potassium persulfate was then added to initiate the polymerization reaction 2. The reaction temperature was controlled at 70°C and the reaction time was 4 hours. The final product was a polyethyleneimine graft copolymer.

[0061] The auxiliary inhibitor is a mixture of 20 parts of sodium chloride, 30 parts of potassium chloride, 30 parts of sodium formate and 20 parts of potassium formate, by mass.

[0062] The raw materials of the dispersant are, by weight, 100 parts of deionized water, 30 parts of ethanolamine, 30 parts of itaconic anhydride, 5 parts of vinylphosphonic acid, 5 parts of N-vinylpyrrolidone and 1.0 part of ammonium persulfate.

[0063] The preparation method of the above dispersant is: First, ethanolamine was added to a four-necked flask, and the temperature was raised to 75°C in a water bath under stirring conditions, and nitrogen was passed to deoxygenate, and then itaconic anhydride was slowly added to carry out an amidation reaction, and the reaction temperature was controlled at 90°C and the reaction time was 4 hours to obtain an intermediate product; Secondly, the flask containing the intermediate product was cooled to room temperature, and deionized water, vinylphosphonic acid and N-vinylpyrrolidone were slowly added thereto, stirred for 30 minutes, and nitrogen was passed to deoxygenate. Then, ammonium persulfate was added to initiate the polymerization reaction 3, and the reaction temperature was controlled at 80°C and the reaction time was 3 hours. Finally, the product obtained was the dispersant.

[0064] The lubricant is a mixture of 45 parts of polyethylene glycol borate, 50 parts of fatty alcohol polyoxyethylene ether and 5 parts of nano silicon nitride by weight.

[0065] The drilling fluid density prepared in this example is 1.3 g / cm 3 , the hot rolling temperature of the drilling fluid is 60℃. Example 3

[0066] A desulfonated low-viscosity high-shear strength inhibited water-based drilling fluid, the raw materials of which are as follows by weight: Fresh water: 100 parts pH adjuster: 0.75 parts Cutting agent: 0.6 parts Fluid loss reducer: 3 parts Inhibitor: 3 parts Auxiliary inhibitor: 10 parts Dispersant: 2 parts Lubricant: 2 parts Barite: Add weight to the drilling fluid density of 1.5g / cm 3 Wherein, the pH adjuster is a mixture of 50 parts of sodium hydroxide and 50 parts of sodium carbonate by mass.

[0067] The cutting agent is a mixture of 25 parts of sclerotium gum, 25 parts of diutan gum and 50 parts of welan gum by weight.

[0068] The raw materials of the fluid loss reducer are as follows: 20 parts of fulvic acid, 100 parts of deionized water, 2 parts of chitosan, 2 parts of γ-methacryloxypropyltrimethoxysilane, 100 parts of 85% ethanol aqueous solution (1% acetic acid), 7.5 parts of acrylic acid, 15 parts of N-vinyl pyrrolidone, 8.5 parts of dimethyldiallylammonium chloride and 0.2 parts of ammonium persulfate by mass. The preparation method of the above-mentioned fluid loss reducing agent is: First, dissolve fulvic acid in deionized water, stir for 45 minutes, then add chitosan, continue stirring for 1.5 hours, and transfer the fulvic acid-chitosan mixture to a four-necked round-bottom flask. Then dissolve γ-methacryloxypropyltrimethoxysilane in an 85% ethanol aqueous solution containing 1% acetic acid, then slowly heat to 45°C under stirring conditions, and hydrolyze for 4 hours; then slowly add the pre-hydrolyzed silane coupling agent to the fulvic acid-chitosan mixture, continue stirring and heat to 65°C, stop heating after 15 hours of reaction, and cool to room temperature; remove the solvent by centrifugation, wash with anhydrous ethanol several times, and then vacuum dry to obtain the intermediate product; Secondly, acrylic acid, N-vinyl pyrrolidone and dimethyldiallylammonium chloride were dissolved in deionized water in advance, and the pH value was adjusted to 7.5 with 0.1 mol / L sodium hydroxide aqueous solution. After stirring for 20 minutes, the mixed solution was transferred to a four-necked round-bottom flask; then, the intermediate product obtained in the above step was added thereto under stirring, nitrogen was passed to deoxygenate, the temperature was raised to 70°C, and ammonium persulfate was dissolved in deionized water and then added dropwise thereto to initiate a polymerization reaction for 1, which lasted for 4 hours, then the reaction was stopped and cooled to room temperature; finally, the mixture was washed with deionized water for multiple times, vacuum filtered, vacuum dried and crushed, and the obtained product was a filtrate reducer.

[0069] The inhibitor is a mixture of 75 parts of polyethyleneimine graft copolymer and 25 parts of hexamethylenediamine by mass; The raw materials of the polyethyleneimine graft copolymer are as follows: 100 parts of deionized water, 50 parts of polyethyleneimine, 15 parts of maleic anhydride, 20 parts of dimethyldiallylammonium chloride and 0.7 parts of potassium persulfate, by weight. The preparation method of the above-mentioned polyethyleneimine graft copolymer is: First, polyethyleneimine was added to a four-necked flask, and the temperature was raised to 70°C in a water bath under stirring conditions, and nitrogen was passed to deoxygenate, and then maleic anhydride was slowly added to carry out amidation reaction, and the reaction temperature was controlled at 75°C and the reaction time was 4 hours to obtain an intermediate product; Secondly, the flask containing the intermediate product was cooled to room temperature, and deionized water and dimethyldiallyl ammonium chloride were slowly added thereto, stirred for 45 minutes, nitrogen was passed to deoxygenate, and potassium persulfate was then added to initiate polymerization reaction 2, and the reaction temperature was controlled at 65°C, the reaction time was 3 hours, and the final product was polyethyleneimine graft copolymer.

[0070] The auxiliary inhibitor is a mixture of 15 parts of sodium chloride, 25 parts of potassium chloride, 35 parts of sodium formate and 25 parts of potassium formate, by mass.

[0071] The raw materials of the dispersant are, by mass, 100 parts of deionized water, 25 parts of ethanolamine, 25 parts of itaconic anhydride, 4 parts of vinylphosphonic acid, 4 parts of N-vinylpyrrolidone and 0.75 parts of ammonium persulfate; The preparation method of the dispersant is: First, ethanolamine was added to a four-necked flask, and the temperature was raised to 72°C in a water bath under stirring conditions, and nitrogen was passed to deoxygenate, and then itaconic anhydride was slowly added to carry out an amidation reaction, and the reaction temperature was controlled at 85°C and the reaction time was 3h to obtain an intermediate product; Secondly, the flask containing the intermediate product was cooled to room temperature, and deionized water, vinylphosphonic acid and N-vinylpyrrolidone were slowly added thereto, stirred for 25 minutes, and nitrogen was passed to deoxygenate. Then, ammonium persulfate was added to initiate the polymerization reaction 3, and the reaction temperature was controlled at 75°C. The reaction time was 2.5 hours, and the final product was the dispersant.

[0072] Calculated by mass fraction, the lubricant is a mixture of 42.5 parts by mass of polyethylene glycol borate, 47.5 parts by mass of fatty alcohol polyoxyethylene ether and 7.5 parts by mass of nano silicon nitride.

[0073] The drilling fluid density prepared in this example is 1.5 g / cm 3 , the hot rolling temperature of the drilling fluid is 90℃. Example 4

[0074] A desulfonated low-viscosity high-shear strength inhibited water-based drilling fluid, the raw materials of which are as follows by weight: Fresh water: 100 parts pH adjuster: 1.0 part Cutting agent: 0.5 parts Fluid loss reducer: 3.5 parts Inhibitor: 3 parts Auxiliary inhibitor: 5 parts Dispersant: 3 parts Lubricant: 3 parts Barite: Add weight to the drilling fluid density of 1.7g / cm 3 Wherein, the pH adjuster is a mixture of 40 parts of sodium hydroxide and 60 parts of sodium carbonate by mass.

[0075] The cutting agent is a mixture of 30 parts of sclerotium gum, 20 parts of diutan gum and 50 parts of welan gum by weight.

[0076] The raw materials of the fluid loss reducer are as follows: 18 parts of fulvic acid, 100 parts of deionized water, 1.5 parts of chitosan, 2 parts of γ-methacryloxypropyltrimethoxysilane, 100 parts of 85% ethanol aqueous solution (1% acetic acid), 6 parts of acrylic acid, 12 parts of N-vinyl pyrrolidone, 6 parts of dimethyldiallylammonium chloride and 0.1 parts of ammonium persulfate by mass. The preparation method of the above-mentioned fluid loss reducing agent is: First, dissolve fulvic acid in deionized water, stir for 40 minutes, then add chitosan, continue stirring for 1 hour, and transfer the fulvic acid-chitosan mixture to a four-necked round-bottom flask. Then dissolve γ-methacryloxypropyltrimethoxysilane in 85% ethanol aqueous solution containing 1% acetic acid, then slowly heat to 42°C under stirring conditions, and hydrolyze for 3.5 hours; then slowly add the pre-hydrolyzed silane coupling agent to the fulvic acid-chitosan mixture, continue stirring and heat to 63°C, stop heating after 12 hours of reaction, and cool to room temperature; remove the solvent by centrifugation, wash with anhydrous ethanol several times, and then vacuum dry to obtain the intermediate product; Secondly, acrylic acid, N-vinyl pyrrolidone and dimethyldiallylammonium chloride were dissolved in deionized water in advance, and the pH value was adjusted to 7 with 0.1 mol / L sodium hydroxide aqueous solution. After stirring for 16 minutes, the mixed solution was transferred to a four-necked round-bottom flask; then, the intermediate product obtained in the above step was added thereto under stirring, nitrogen was passed to deoxygenate, the temperature was raised to 68°C, and ammonium persulfate was dissolved in deionized water and then added dropwise thereto to initiate a polymerization reaction 1, which lasted for 3.5 hours, then the reaction was stopped and cooled to room temperature; finally, after washing with deionized water for multiple times, vacuum filtration, vacuum drying and crushing were performed, and the obtained product was a filtrate reducer.

[0077] The inhibitor is a mixture of 72 parts of polyethyleneimine graft copolymer and 28 parts of hexamethylenediamine by weight; The raw materials of the polyethyleneimine graft copolymer are as follows: 100 parts of deionized water, 55 parts of polyethyleneimine, 18 parts of maleic anhydride, 15 parts of dimethyldiallylammonium chloride and 0.6 parts of potassium persulfate, by weight. The preparation method of the above-mentioned polyethyleneimine graft copolymer is: First, polyethyleneimine was added to a four-necked flask, and the temperature was raised to 68°C in a water bath under stirring conditions, and nitrogen was passed to deoxygenate, and then maleic anhydride was slowly added to carry out amidation reaction, and the reaction temperature was controlled at 76°C and the reaction time was 5 hours to obtain an intermediate product; Secondly, the flask containing the intermediate product was cooled to room temperature, and deionized water and dimethyldiallyl ammonium chloride were slowly added thereto, stirred for 40 minutes, and nitrogen was passed to deoxygenate. Potassium persulfate was then added to initiate the polymerization reaction 2, and the reaction temperature was controlled at 66°C. The reaction time was 2 hours, and the final product was a polyethyleneimine graft copolymer.

[0078] The auxiliary inhibitor is a mixture of 20 parts of sodium chloride, 20 parts of potassium chloride, 35 parts of sodium formate and 25 parts of potassium formate, by mass.

[0079] The raw materials of the dispersant are, by mass, 100 parts of deionized water, 26 parts of ethanolamine, 30 parts of itaconic anhydride, 3 parts of vinylphosphonic acid, 5 parts of N-vinylpyrrolidone and 0.8 parts of ammonium persulfate; The above dispersant preparation method is: First, ethanolamine was added to a four-necked flask, and the temperature was raised to 73°C in a water bath under stirring conditions, and nitrogen was passed to deoxygenate, and then itaconic anhydride was slowly added to carry out an amidation reaction, and the reaction temperature was controlled at 86°C and the reaction time was 3.5h to obtain an intermediate product; Secondly, the flask containing the intermediate product was cooled to room temperature, and deionized water, vinylphosphonic acid and N-vinylpyrrolidone were slowly added thereto, stirred for 28 minutes, and nitrogen was passed to deoxygenate. Subsequently, ammonium persulfate was added to initiate the polymerization reaction 3, and the reaction temperature was controlled at 76°C. The reaction time was 2 hours, and the final product was the dispersant.

[0080] The lubricant is a mixture of 40 parts of polyethylene glycol borate, 50 parts of fatty alcohol polyoxyethylene ether and 10 parts of nano silicon nitride by weight.

[0081] The drilling fluid density prepared in this example is 1.7 g / cm 3 , the hot rolling temperature of the drilling fluid is 120℃. Example 5

[0082] A desulfonated low-viscosity high-shear strength inhibited water-based drilling fluid, the raw materials of which are as follows, calculated by weight: Fresh water: 100 parts pH adjuster: 0.8 parts Cutting agent: 0.6 parts Fluid loss reducer: 4 parts Inhibitor: 4 parts Auxiliary inhibitor: 15 parts Dispersant: 2 parts Lubricant: 3 parts Barite: Add weight to the drilling fluid density of 1.7g / cm 3 Wherein, the pH adjuster is a mixture of 50 parts of sodium hydroxide and 50 parts of sodium carbonate by mass.

[0083] The cutting agent is a mixture of 25 parts of sclerotium gum, 30 parts of diutan gum and 45 parts of welan gum by weight.

[0084] The raw materials of the fluid loss reducer are as follows: 25 parts of fulvic acid, 100 parts of deionized water, 1 part of chitosan, 2 parts of γ-methacryloxypropyltrimethoxysilane, 100 parts of 85% ethanol aqueous solution (1% acetic acid), 8 parts of acrylic acid, 16 parts of N-vinyl pyrrolidone, 10 parts of dimethyldiallylammonium chloride and 0.2 parts of ammonium persulfate by mass. The preparation method of the above-mentioned fluid loss reducing agent is: First, dissolve fulvic acid in deionized water, stir for 50 minutes, then add chitosan, continue stirring for 2 hours, and transfer the fulvic acid-chitosan mixture to a four-necked round-bottom flask. Then dissolve γ-methacryloxypropyltrimethoxysilane in an 85% ethanol aqueous solution containing 1% acetic acid, then slowly heat to 48°C under stirring conditions, and hydrolyze for 5 hours; then slowly add the pre-hydrolyzed silane coupling agent to the fulvic acid-chitosan mixture, continue stirring and heat to 66°C, stop heating after 18 hours of reaction, and cool to room temperature; remove the solvent by centrifugation, wash with anhydrous ethanol several times, and then vacuum dry to obtain the intermediate product; Secondly, acrylic acid, N-vinyl pyrrolidone and dimethyldiallylammonium chloride were dissolved in deionized water in advance, and the pH value was adjusted to 8 with 0.1 mol / L sodium hydroxide aqueous solution. After stirring for 18 minutes, the mixed solution was transferred to a four-necked round-bottom flask; then, the intermediate product obtained in the above step was added thereto under stirring, nitrogen was passed to deoxygenate, the temperature was raised to 72°C, and ammonium persulfate was dissolved in deionized water and then added dropwise thereto to initiate a polymerization reaction for 1, which lasted for 4 hours, then the reaction was stopped and cooled to room temperature; finally, the mixture was washed with deionized water for multiple times, vacuum filtered, vacuum dried and crushed, and the obtained product was a filtrate reducer.

[0085] The inhibitor is a mixture of 78 parts of polyethyleneimine graft copolymer and 22 parts of hexamethylenediamine by weight; The raw materials of the polyethyleneimine graft copolymer are, by weight: 100 parts of deionized water, 50 parts of polyethyleneimine, 16 parts of maleic anhydride, 16 parts of dimethyldiallylammonium chloride and 0.7 parts of potassium persulfate; The preparation method of the above-mentioned polyethyleneimine graft copolymer is: First, polyethyleneimine was added to a four-necked flask, and the temperature was raised to 70°C in a water bath under stirring conditions, and nitrogen was passed to deoxygenate, and then maleic anhydride was slowly added to carry out an amidation reaction, and the reaction temperature was controlled at 70°C and the reaction time was 5 hours to obtain an intermediate product; Secondly, the flask containing the intermediate product was cooled to room temperature, and deionized water and dimethyldiallyl ammonium chloride were slowly added thereto, stirred for 30 minutes, nitrogen was passed to deoxygenate, and potassium persulfate was then added to initiate the polymerization reaction 2. The reaction temperature was controlled at 65°C and the reaction time was 2 hours. The final product was a polyethyleneimine graft copolymer.

[0086] The auxiliary inhibitor is a mixture of 15 parts of sodium chloride, 30 parts of potassium chloride, 35 parts of sodium formate and 20 parts of potassium formate, by mass.

[0087] The raw materials of the dispersant are, by mass, 100 parts of deionized water, 20 parts of ethanolamine, 30 parts of itaconic anhydride, 5 parts of vinylphosphonic acid, 3 parts of N-vinylpyrrolidone and 0.6 parts of ammonium persulfate; The preparation method of the dispersant is: First, ethanolamine was added to a four-necked flask, and the temperature was raised to 70°C in a water bath under stirring conditions, and nitrogen was passed to deoxygenate, and then itaconic anhydride was slowly added to carry out an amidation reaction, and the reaction temperature was controlled at 80°C and the reaction time was 4 hours to obtain an intermediate product; Secondly, the flask containing the intermediate product was cooled to room temperature, and deionized water, vinylphosphonic acid and N-vinylpyrrolidone were slowly added thereto, stirred for 30 minutes, and nitrogen was passed to deoxygenate. Then, ammonium persulfate was added to initiate the polymerization reaction 3, and the reaction temperature was controlled at 80°C and the reaction time was 2 hours. Finally, the product obtained was the dispersant.

[0088] The lubricant is a mixture of 40 parts of polyethylene glycol borate, 45 parts of fatty alcohol polyoxyethylene ether and 15 parts of nano silicon nitride by weight.

[0089] The drilling fluid density prepared in this example is 1.7 g / cm 3 , the hot rolling temperature of the drilling fluid is 150℃. Comparative Example 1

[0090] The commonly used polysulfonated water-based drilling fluid on site is composed of 100 parts of fresh water, 3 parts of bentonite, 1.0 part of pH regulator (the mass ratio of sodium hydroxide and sodium carbonate is 1:1), 5 parts of potassium chloride, 0.5 parts of zwitterionic polymer strong coating agent, 0.6 parts of low-viscosity carboxymethyl cellulose, 3 parts of sulfonated lignite resin, 3 parts of sulfonated asphalt, 3 parts of sulfonated phenolic resin, 3 parts of modified vegetable oil, and barite is added to a density of 1.7g / cm 3 The hot rolling temperature of the drilling fluid obtained in this comparative example is 150°C.

[0091] The drilling fluids obtained in the above embodiments and comparative examples were evaluated according to GB / T16783.1-2014 "Field Test of Drilling Fluids in Petroleum and Natural Gas Industry Part 1: Water-Based Drilling Fluids", and the biodegradability and sulfur content were tested with reference to SY / T 7467-2020 "Technical Specifications for Environmental Performance Evaluation of Drilling Fluids" and SN / T 3005-2011 "Elemental Analyzer Determination of Carbon, Hydrogen, Nitrogen and Sulfur Content in Organic Chemicals". The results are shown in Table 1.

[0092] Table 1 Comprehensive properties of drilling fluid , Note: ρ: drilling fluid density, g / cm 3 T: Drilling fluid aging temperature, °C AV: drilling fluid apparent viscosity, mPa·s PV: drilling fluid plastic viscosity, mPa·s YP: Drilling fluid dynamic shear force, Pa YP / PV: Dynamic plastic ratio, Pa / mPa·s Φ3: Six-speed rotary viscometer 3-turn reading, dimensionless API: Drilling fluid medium pressure loss (0.7MPa, room temperature, 30min), mL EP: Extreme pressure friction coefficient, dimensionless η: Apparent viscosity increase rate after 20% sodium-based bentonite contamination, % θ: Shale rolling recovery rate, % δ: Sulfur content on dry basis of unweighted drilling fluid, % BI: Drilling fluid biodegradation index, % It can be seen from Examples 1 to 5 that the desulfonated low viscosity high shear strength inhibiting water-based drilling fluid has a density of 1.1 to 1.7 g / cm 3range, and the aging temperature is in the range of 30~150℃, all of which have good low-viscosity and high-shear rheological properties, filtration control properties, lubrication properties, inhibition properties and environmentally friendly biodegradability. It can be seen from Example 5 and Comparative Example 1 that compared with the commonly used polysulfonated water-based drilling fluid on site, the desulfonated low-viscosity and high-shear inhibition water-based drilling fluid has significantly lower plastic viscosity and higher dynamic shear force, and the dynamic-plastic ratio is greater than 1.0 Pa / mPa·s, showing better suspension and rock-carrying performance, and better lubrication performance, extreme pressure friction coefficient <0.1, which is more suitable for horizontal well drilling operations. In terms of inhibition, after being contaminated with 20% sodium-based bentonite, the desulfonated low-viscosity and high-shear inhibition water-based drilling fluid has a more stable viscosity, and the apparent viscosity increase rate is less than 11%, while the apparent viscosity increase rate of the polysulfonated water-based drilling fluid exceeds 45%, which is significantly thickened. In addition, the biodegradation index of the desulfonated low-viscosity and high-shear strength inhibited water-based drilling fluid is much higher than 5%, and it has excellent biodegradability. At the same time, the dry basis sulfur content is 0 without considering barite, which is friendly to the ecological environment. Under the same conditions, the biodegradation index of the polysulfonated water-based drilling fluid is less than 5%, and its biodegradability is poor. Moreover, the dry basis sulfur content reaches 4.07% without considering barite. Even if waste treatment is carried out, toxic and harmful sulfur-containing by-products will be produced, which is not conducive to environmental protection.

[0093] The five groups of embodiments of the desulfonated low-viscosity and high-shear strength inhibiting water-based drilling fluid of the present invention, after aging at different densities and different temperatures: have excellent rheological properties, low plastic viscosity, and dynamic-plastic ratios all higher than 1.0, showing significant suspension rock-carrying performance; low API filtration loss, all of which do not exceed 3.5 mL; the extreme pressure friction coefficient is significantly lower than 0.1, with excellent lubrication performance, which is beneficial to reducing friction torque and is suitable for horizontal well operations; the apparent viscosity increase rate after 20% sodium-based bentonite contamination is lower than 11%, and the shale rolling recovery rate is higher than 95%, and the hydration inhibition effect on clay is significant; at the same time, the biodegradation index is greater than 25%, and the unweighted dry basis sulfur content is 0, with significant environmentally friendly biodegradable performance, and harmless to the ecological environment.

[0094] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A desulfonated low-viscosity high-shear strength inhibited water-based drilling fluid, characterized in that: The raw materials include, by weight: 100 parts of water, 0.5-1.0 parts of pH regulator, 0.5-0.7 parts of shearing agent, 2-4 parts of fluid loss reducer, 2-4 parts of inhibitor, 5-15 parts of auxiliary inhibitor, 1-3 parts of dispersant, 1-3 parts of lubricant and barite; the barite is not limited in weight and is added until the required density is reached; The cutting agent is a mixture of 20 to 30 parts of sclerotium gum, 20 to 30 parts of diutan gum and 40 to 60 parts of welan gum.

2. The desulfonated low-viscosity and high-shear-inhibiting water-based drilling fluid according to claim 1, characterized in that: The pH adjuster is a mixture of 40 to 60 parts of sodium hydroxide and 40 to 60 parts of sodium carbonate by mass.

3. The desulfonated low-viscosity and high-shear strength inhibited water-based drilling fluid according to claim 1, characterized in that: The raw materials of the fluid loss reducer include, by mass: 15-25 parts of fulvic acid, 100 parts of water, 1-3 parts of chitosan, 1-3 parts of γ-methacryloxypropyltrimethoxysilane, 100 parts of ethanol aqueous solution containing acetic acid, 5-10 parts of acrylic acid, 10-20 parts of N-vinyl pyrrolidone, 5-12 parts of dimethyldiallylammonium chloride and 0.1-0.3 parts of ammonium persulfate; The preparation method of the fluid loss reducer comprises the following steps: dissolving chitosan in a fulvic acid aqueous solution to obtain a fulvic acid-chitosan mixed solution; Dissolving γ-methacryloxypropyltrimethoxysilane in an ethanol aqueous solution containing acetic acid, and then performing a hydrolysis reaction to obtain a pre-hydrolyzed silane coupling agent; Adding the pre-hydrolyzed silane coupling agent to the fulvic acid-chitosan mixed solution to react and obtain an intermediate product; Acrylic acid, N-vinyl pyrrolidone and dimethyl diallyl ammonium chloride are dissolved in water, and the pH value is adjusted to alkaline, and then the intermediate product is added under stirring conditions. Under the protection of an inert atmosphere, ammonium persulfate is added to the reaction system to carry out a polymerization reaction 1 to obtain the fluid loss reducer.

4. The desulfonated low-viscosity and high-shear strength inhibited water-based drilling fluid according to claim 1, characterized in that: The inhibitor is a mixture of 70-80 parts of polyethyleneimine graft copolymer and 20-30 parts of hexamethylenediamine by weight.

5. The desulfonated low-viscosity and high-shear-strength inhibited water-based drilling fluid according to claim 4, characterized in that: The raw materials of the polyethyleneimine graft copolymer include, by weight: 100 parts of water, 40-60 parts of polyethyleneimine, 10-20 parts of maleic anhydride, 15-25 parts of dimethyldiallylammonium chloride and 0.6-0.8 parts of potassium persulfate.

6. The desulfonated low-viscosity and high-shear-inhibiting water-based drilling fluid according to claim 5, characterized in that: The preparation method of the polyethyleneimine graft copolymer comprises the following steps: Conducting amidation reaction between polyethyleneimine and maleic anhydride; After the amidation reaction is completed, water and dimethyldiallylammonium chloride are added to the reaction system, and potassium persulfate is added under an inert atmosphere to carry out polymerization reaction 2 to obtain the polyethyleneimine graft copolymer.

7. The desulfonated low-viscosity and high-shear-inhibiting water-based drilling fluid according to claim 1, characterized in that: In terms of weight, the auxiliary inhibitor is a mixture of 10 to 20 parts of sodium chloride, 20 to 30 parts of potassium chloride, 30 to 40 parts of sodium formate and 20 to 30 parts of potassium formate.

8. The desulfonated low-viscosity and high-shear-strength inhibited water-based drilling fluid according to claim 1, characterized in that: The raw materials of the dispersant include, by weight: 100 parts of water, 20-30 parts of ethanolamine, 20-30 parts of itaconic anhydride, 3-5 parts of vinylphosphonic acid, 3-5 parts of N-vinylpyrrolidone and 0.5-1.0 parts of ammonium persulfate; The preparation method of the dispersant comprises the following steps: Conducting an amidation reaction between ethanolamine and itaconic anhydride; After the amidation reaction is completed, water, vinylphosphonic acid and N-vinyl pyrrolidone are added to the reaction system, and potassium persulfate is added under an inert atmosphere to carry out polymerization reaction 3 to obtain the dispersant.

9. The desulfonated low-viscosity and high-shear-strength inhibited water-based drilling fluid according to claim 1, characterized in that: The lubricant is a mixture of 40-45 parts of polyethylene glycol borate, 45-50 parts of fatty alcohol polyoxyethylene ether and 5-15 parts of nano silicon nitride in parts by mass.

Citation Information

Patent Citations

  • Method for preparing water-soluble cross-linked polymer grafted carbon nano tube

    CN101735416A

  • Method for preparing branched filtrate reducer used for water-based drilling fluid

    CN108219759A

  • High-temperature-resistant organic / inorganic hybrid polymer filtrate reducer and preparation method thereof

    CN112457454A

  • Drilling fluid as well as preparation method and application thereof

    CN113861953A

  • Non-sulfonated high-temperature-resistant water-based drilling fluid

    CN114891489A

Cited By

  • High-temperature-resistant environment-friendly drilling fluid filtrate reducer based on humic acid and sodium alginate and preparation method of high-temperature-resistant environment-friendly drilling fluid filtrate reducer

    CN120865859A

  • A high-temperature-resistant environment-friendly drilling fluid filtrate reducer based on humic acid and sodium alginate and a preparation method thereof

    CN120865859B